Postural correlates of visual incentives: application to food and alcohol stimuli - Duman, Duygu; Kızılışık, Sumeyye; Zitouni, Amel; Campanella, Salvatore; Lelard, Thierry; Akounach, Mbarka; Mouras, Harold (Frontiers in Psychology, 2025)
IntroductionAlcohol consumption is a major public health concern, linked to numerous diseases, including neurological disorders. Building on research into the interaction between emotion and motor processes, posturography has proven useful for studying how socioaffective information influences body sway. Few studies have explored this under motivational conditions, with limited work on food or alcohol cues.MethodsFifty-five healthy participants viewed visual stimuli in four conditions (neutral–alcohol, alcohol, neutral–food, food) while their postural responses were recorded. After the experiment, participants rated each stimulus on pleasantness, unpleasantness, consumption, approach, avoidance, and intensity.ResultsSubjective ratings differed significantly between conditions. Postural variability and movement amplitude were modulated by both incentive type (food vs. alcohol) and valence (incentive vs. neutral). Notably, food cues increased postural movement, whereas alcohol cues decreased it.DiscussionThese findings highlight distinct motor signatures for different appetitive cues and contribute to understanding how emotions and motivation shape embodied responses to environmental stimuli.